2019
DOI: 10.1007/s11789-019-00096-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a)—antisense therapy

Abstract: Elevated levels of lipoprotein(a) (Lp(a)) contribute to the risk of early and severe cardiovascular disease (CVD) and Lp(a) is acknowledged as a risk factor to be included in risk assessment. The established lipid-modifying medical therapies do not lower Lp(a) except niacin but no data of endpoint trials are available. Of the new lipid-modifying drugs a few have some impact on Lp(a). Whether the Lp(a) lowering effect contributes to the reduction of CVD events would have to be shown in Lp(a) dedicated trials. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
(54 reference statements)
0
4
0
1
Order By: Relevance
“…Some trials and data from registries show that regular apheresis effectively reduces CV events (63). The results of 5 years of prospective follow-up confirmed that Lp(a) apheresis has a lasting effect on the prevention of CV events in patients with hyperlipoproteinemia (a), reducing the mean annual cardiovascular event rate by up to 80% (64,65).…”
Section: Lp(a) Apheresismentioning
confidence: 85%
See 1 more Smart Citation
“…Some trials and data from registries show that regular apheresis effectively reduces CV events (63). The results of 5 years of prospective follow-up confirmed that Lp(a) apheresis has a lasting effect on the prevention of CV events in patients with hyperlipoproteinemia (a), reducing the mean annual cardiovascular event rate by up to 80% (64,65).…”
Section: Lp(a) Apheresismentioning
confidence: 85%
“…As already mentioned, mipomersen, an ASO which markedly inhibits mRNA of apoB, does not affect the production of apo(a), but could lower Lp(a) by influencing the Lp(a) assembly. The ASO by which we can inhibit apo(a) synthesis in the liver is currently the only available approach for specific Lp(a) lowering (84,85). Being injected subcutaneously, they enter the circulation and bind to plasma proteins, while after entering the liver, they accumulate in the hepatocytes.…”
Section: Emerging Treatment Possibilities With Rna-targeted Therapiesmentioning
confidence: 99%
“…The general siRNA therapeutic strategy is to load RISC with synthetic antisense (AS) sequences to downregulate a specific target RNA of clinical relevance. Therapeutic targets have included mRNA, pre-mRNA, long noncoding RNA (lncRNA), and viral and bacterial RNA. Similar to ASOs, RNA target selection is guided by identifying pathological situations; for example, where an overabundance of protein or RNA is expressed, expanded RNA repeats are present, spliceopathy exists, or a genetic mutation in one or both alleles leads to production of a dysfunctional RNA or protein. …”
Section: Part 1: Therapeutic Strategy and Sar In Drug Developmentmentioning
confidence: 99%
“…Research in the lipoprotein field has led to the recent development of an antisense oligonucleotide against apo(a), AKCEA-APO(a)-LRx, which selectively decreases Lp(a) concentrations by approximately 80% [28].…”
Section: New Lipid-lowering Treatments Specifically Targeting Lp(a)mentioning
confidence: 99%